SCIENTIFIC APPROACH OF 2013 CURRICULUM: TEACHERS’ IMPLEMENTATION IN ENGLISH LANGUAGE TEACHING - Sri Ratnaningsih (University of Kuningan, 2017)
The research is aimed at investigating the teachers’ implementation of scientific approach in English Language Teaching in one state junior high school in Bandung Regency. In addition, this research discusses the conformation of the Scientific Approach implementation and the lesson plans based on the 2013 curriculum. This research employs a case study qualitative research design. The data were obtained from classroom observation and teachers’ lesson plan analysis and interview. The findings showed that the teachers implemented the scientific stages in English Language Teaching. They conducted observing, questioning, experimenting, associating and communicating in the sequence activities. Besides, the teachers can demonstrate the student-centered learning strengthened by collaborative, cooperative, active and meaningful learning. However, concerning the conformation of the implementation with lesson plans, based on the indicators, learning objectives, learning materials, learning media, scientific stages and Scientific Approach model (discovery learning, inquiry leaning, problem based learning and project based learning), the teachers still have to underline and mention the Scientific Approach model and state learning objectives. Furthermore, the other components have been presented well in both teaching and lesson plans.Keywords: English language teaching, lesson plan, scientific approach, teaching practice, the 2013 curriculum